2012
DOI: 10.1117/1.jbo.17.5.056014
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared spectroscopic imaging of cardiac tissue to detect collagen deposition after myocardial infarction

Abstract: Abstract. Myocardial infarction often leads to an increase in deposition of fibrillar collagen. Detection and characterization of this cardiac fibrosis is of great interest to investigators and clinicians. Motivated by the significant limitations of conventional staining techniques to visualize collagen deposition in cardiac tissue sections, we have developed a Fourier transform infrared imaging spectroscopy (FT-IRIS) methodology for collagen assessment. The infrared absorbance band centered at 1338 cm −1 , wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 42 publications
0
41
0
Order By: Relevance
“…In this case, the size of collagen scarring decreased from 18.7 to 1.6 % as revealed by the FtIR technique and was comparable to the staining results. these findings demonstrate that FtIR imaging can be a powerful labelfree tool in the evaluation of collagen deposition and remodelling after myocardial infarction [148]. the observation of collagen fibrosis by using FtIR imaging has been also reported for the cardiomyopathy induced by an infection with coxsackievirus, recognized as a highly active etiological agent in the development of myocarditis [149].…”
Section: Cardiac Tissuementioning
confidence: 89%
See 2 more Smart Citations
“…In this case, the size of collagen scarring decreased from 18.7 to 1.6 % as revealed by the FtIR technique and was comparable to the staining results. these findings demonstrate that FtIR imaging can be a powerful labelfree tool in the evaluation of collagen deposition and remodelling after myocardial infarction [148]. the observation of collagen fibrosis by using FtIR imaging has been also reported for the cardiomyopathy induced by an infection with coxsackievirus, recognized as a highly active etiological agent in the development of myocarditis [149].…”
Section: Cardiac Tissuementioning
confidence: 89%
“…FtIR monitoring of the treatment of infarcted rat myocardium by targeted delivery of vascular endothelial growth factor (vEgF) has been reported by Cheheltani et al [148]. here, collagen deposition in the infarct zone of the left ventricles was mapped using the integrated intensity of a band at 1338 cm −1 , because only this IR maximum was found to be specific for collagen in the investigated tissue sections [148].…”
Section: Cardiac Tissuementioning
confidence: 97%
See 1 more Smart Citation
“…Many studies demonstrated high sensitivity of FT-IR to analyze the skeletal muscle (Jerônimo et al, 2012), heart muscle (Cheheltani et al 2012), and some biological fluids, such as serum (Carvalho et al, 2014), urine (Khaskheli et al, 2013), and saliva (Khaustova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations have searched for the spectral signatures of collagen within human tissues in such diverse contexts as gliomas (Noreen et al, 2012), cardiomyopathy (Gough et al, 2003; Wang et al, 2005), myocardial infarction (Cheheltani et al, 2012), wound healing (Wiens et al, 2007), and articular cartilage (Saarakkala et al, 2010). It has also been suggested that serum can be measured using FT-IR as a surrogate for hepatic fibrosis (Scaglia et al, 2011).…”
Section: Fibrosis As the Target Regionmentioning
confidence: 99%